Diketopyrrolopyrrole Based Organic Semiconductor Materials for Field-Effect Transistors - Zou, Xiangyu; Cui, Shuaiwei; Li, Junqiang; Wei, Xueling; Zheng, Meng (Frontiers in Chemistry, 2021)
Over the past several decades, organic conjugated materials as semiconductors in organic field effect transistors (OFETs) have attracted more and more attentions from the scientific community due to their intriguing properties of mechanical flexibility and solution processability. Except the device fabrication technique, design and synthesis novel organic semiconductor materials with high charge carries mobility is crucial for the development of high-performance OFETs. In the past few years, more and more novel materials were designed and tested in the OFETs. Among which, diketopyrrolopyrrole (DPP) and its derivatives, as the the electron acceptors to build donor-acceptor (D-A) typed materials, are the perspective. In this article, recently reported molecules regarding to the DPP derivatives for OFETs application are reviewed. In addition, the relationship between the chemical structures and the performance of the device are discussion. Further more, an outlook of DPP-based materials in OFETs with future design concept and the development trend are provide.